3
$\begingroup$

I have the series
$$\sum_{k=1}^{N-1}\frac{1}{1-w_k} $$ where $w_k=e^{\frac{2\pi i k}{N}}$, how can I find the summation of this , another question related to this sum
$$\sum_{k=1}^{N-1}\frac{1}{z-w_k} $$

$\endgroup$
3
$\begingroup$

Let $P(z)=z^{N}-1$. Then $$P(z)=\prod_{k=0}^{N-1}(z-w_{k})$$ where $w_{0}=1$. From here, it is easy to check that $$ \sum_{k=0}^{N-1}\frac{1}{z-w_{k}}=\frac{P^{\prime}(z)}{P(z)}% $$ hence $$ \sum_{k=1}^{N-1}\frac{1}{z-w_{k}}=\frac{P^{\prime}(z)}{P(z)}-\frac{1}{z-1}=\frac{Nz^{N-1}}{z^{N}-1}-\frac{1}{z-1}=\frac{(N-1)z^{N}-Nz^{N-1}+1}{(z^{N}-1)(z-1)}\text{.} $$ In particular, for $z=1$: $$ S:=\sum_{k=1}^{N-1}\frac{1}{1-w_{k}}=\lim_{z\rightarrow1}\frac{(N-1)z^{N}-Nz^{N-1}+1}{(z^{N}-1)(z-1)}. $$ In order to compute the limit, we write is as a limit at $0$, i.e., let $z=w+1$, $w\rightarrow0$, hence $$ S=\lim_{w\rightarrow0}\frac{(N-1)(w+1)^{N}-N(w+1)^{N-1}+1}{w((w+1)^{N}-1)}. $$ Next, recall that $$ \lim_{w\rightarrow0}\frac{(w+1)^{N}-1}{w}=N $$ hence $$ S=\frac{1}{N}\cdot\lim_{w\rightarrow0}\frac{(N-1)(w+1)^{N}-N(w+1)^{N-1}+1}{w^{2}}. $$ The last step is to apply l'Hopital's rule, hence \begin{align*} S & =\frac{1}{N}\cdot\lim_{w\rightarrow0}\frac{\left( (N-1)(w+1)^{N}-N(w+1)^{N-1}+1\right) ^{\prime}}{\left( w^{2}\right) ^{\prime}}=\frac{1}{N}\cdot\lim _{w\rightarrow0}\frac{N(N-1)(w+1)^{N-2}w}{2w}\\ & =\frac{1}{N}\cdot\lim_{w\rightarrow0}\frac{N(N-1)}{2}(w+1)^{N-2}=\frac{N-1}{2}. \end{align*}

$\endgroup$
1
$\begingroup$

$$\frac{1}{1-w^{r}}+\frac{1}{1-w^{n-r}}=\frac{2-w^{r}-w^{n-r}}{2-w^{r}-w^{n-r}}=1$$ where $w=e^{i2\pi/n}$

If you continue cancelling in pairs the sum will turn out to be = $\dfrac{N-1}{2}$

In case you have a middle term ,the term = $\dfrac{1}{1-e^{i\pi/2}}=\dfrac{1}{2}$

$\endgroup$
  • $\begingroup$ You don't need to worry about the middle term. Do the sum twice, once with r and once with n-r. The sum of the two is n-1, so each is (n-1)/2. $\endgroup$ – marty cohen Feb 24 at 6:53
0
$\begingroup$

The answer for the first sum is $$\sum_{k=1}^{N-1}\frac{1}{1-w_k}=\frac{N-1}{2}$$

And for the second: $$\sum_{k=1}^{N-1}\frac{1}{z-w_k} = \sum_{k=0}^{N-1}\frac{1}{z-w_k}- \frac{1}{z-1}= \frac{N z^{N-1}}{z^N-1} -\frac{1}{z-1}$$

I believe series expansion in $w_k$, sum over $k$ and then summing back the series wll give you the above results.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.